Experimental evaluation of cyclic fatigue resistance of four different nickel-titanium instruments after immersion in sodium hypochlorite and/or sterilization - Ureyen Kaya BULEM; Ayse Diljin KECECI; Hilmi Egemen GULDAS (University of São Paulo, 2013)
NiTi instruments have a high risk of separation due to torsional or flexural fatigue (cyclic fatigue). Chemomechanical preparation, cleaning procedures, chemical disinfection and sterilization cause the corrosion of endodontic instruments that may weaken the fracture resistance of the instruments. Objective To assess the effects of NaOCl immersion and autoclave sterilization on the cyclic fatigue resistance of ProFile, FlexMaster, Mtwo and TwistedFiles NiTi instruments (tip size 25, 0.06 taper, n=160). Material and Methods The instruments (n=10 for each subgroup) were dynamically immersed in NaOCl; immersed in NaOCl and sterilized in one autoclave cycle; 5 cycles immersed in NaOCl and sterilized in autoclave and not immersed in NaOCl and not sterilized (control group). Dynamic cyclic fatigue resistance was tested. The number of cycles to failure (NCF) were statistically analyzed (P<0.05). Results Kruskall-Wallis test indicated significant differences among the tested instruments in terms of NCF (P=0.000). The mean NCF of Mtwo (556.75) was higher than that of the Twisted File, Flexmaster and ProFile, 483.1, 376.12, 365.25, respectively. NaOCl immersion and autoclave sterilization have no effect on the NCF values of the tested instruments (P>.05). Conclusions Cyclic fatigue resistance of the tested NiTi instruments cannot be adversely affected by NaOCl immersion and autoclave sterilization. Production process (TwistedFiles) or design (Twisted Files, FlexMaster, Mtwo and ProFile) of the instruments can influence their cyclic fatigue resistance.